A study on knowledge, attitude and practice on disaster preparedness among hospital staff at Ipoh, Perak - Norfarhana Azliya, Ahmad Razali (2018)
The level of knowledge, attitudes and practice (KAP) on disaster preparedness among hospital staff was important as hospital staff is the person who will handle the sudden influx of patient during disasters. The research was conducted at one of the hospital at Ipoh, Perak. This research focused towards the hospital staff to measure the level of KAP among them. The objective of this study is to identify the potential disasters that will occur in the hospital, to measure the level of KAP on disaster preparedness among hospital staff and to determine the critical preparedness factors in the hospital. A descriptive and cross sectional study was conducted to measure the level of KAP on disaster preparedness among hospital staffs (N=212). The questionnaire was distributed to hospital staff from various departments such as the Department of Neurosurgery, Department of Plastic Surgery, Department of Pediatrics and Department of Emergency. While the interview session was conducted with the Head of Public Health Unit on the same day the questionnaire was distributed. The finding of this research indicated that fire was the potential disaster or threat that may occur in the hospital with the highest percentage of 95.3%. The hospital staffs have the high level of knowledge regarding the definition of key disaster terms, disaster plan and drills. The level of attitude of respondents towards disaster preparedness can be concluded as high. However, the level of practice among the hospital staff was moderate. The hospital has all the six elements of critical preparedness factors. As a conclusion, even though hospital staffs have the positive respond toward KAP on disaster preparedness, action for improvement still need to be taken to ensure that all hospital staffs are always ready to face and handle any disaster.